Long-term prognosis of 35 patients with methionine adenosyltransferase deficiency based on newborn screening in China - Tong, Fan; Zhang, Yuchen; Chen, Chi; Zhu, Ling; Lu, Yijun; Zhang, Zhanming; Chen, Ting; Yan, Jiaxuan; Zheng, Jing; Zhao, Xiaoxu; Zhou, Duo; Yang, Xin; et al. (Frontiers in Cell and Developmental Biology, 2023)
Methionine adenosyltransferase deficiency (MATD) is a rare metabolic disorder caused by mono- or biallelic MAT1A mutations, and has yet to be well understood. Of the 4,065,644 neonates screened between Nov. 2010 and Dec. 2021, 35 individuals have been diagnosed with an estimated incidence 1: 116,161 by a cutoff value of methionine 82.7 µmol/L and follow-up over 11 years. MATD patients with autosomal recessive (AR) type had higher clinical and genetic heterogeneity than those with autosomal dominant (AD) type. Fifteen unrelated AD patients harbored one well-known dominant variants, c.791 G>A or c.776 C>T, and were clinically unaffected with a mean plasma methionine (Met) value < 300 μmol/L. Twenty AR cases have unique genotype and presented a wide range of clinical abnormalities from asymptomatic to white matter lesions. Of them, 10 AR patients displayed severe manifestations, such as verbal difficulty, motor delay, development delay, and white matter lesions, with mean Met >500 μmol/L and thereby were treated with a methionine-restricted diet alone or in combination with betaine, folate or vitamin B6, and were healthy finally. Neurological abnormalities were evidenced in two patients (P16 and P27) with Met values > 800 μmol/L by MRI scan. Neurological abnormalities were reversed here by liver transplantation or by the determination of S-adenosylmethionine supplementation. Additionally, 38 variants of MAT1A distributed within patients and carriers, of which 24 were novel and mostly predicted to be damaged. Our findings with an extensive clinical and genetic dataset provided new insights to its diagnosis and treatment and will be helpful for its optimal management in future.